The Fractured Model Study of Low-Permeability Reservoir in Xinli Oil Field - Xue, Yongchao; Wang, Longjun; Zhao, Xiaoliang; Tian, Hua (Frontiers in Earth Science, 2022)
With the development of the petroleum industry, the importance of low-permeability reservoirs becomes clear. The fracture, which serves as the notable characteristic of a low-permeability reservoir, controls the flow system of reservoir fluid and restrains the development effect. Finding ways to recognize the fracture by using the normal data and building the fracture 3-D model are the important and difficult points of low-permeability development. According to this problem, the authors use a helpful probe. First, from similar outcrop and drilling core study of the fractured original model, the knowledge base of the fracture was built. Second, based on the analysis of the principle of dual-later log identification fracture, the core calibration was used to make logging, and using dual-later log, the fracture in wells was recognized. Third, based on the analysis of the principle of the fractal kriging method, the inter-well fractures were predicted. Finally, the 3-D model of fracture was built with fractural random simulation. The result shows that the 3-D model is in accordance with the fact of the development. So, the method is correct.